Tekanan untuk makan dengan kejadian picky eater pada anak usia 2-3 tahun - Carissa Cerdasari; Siti Helmyati; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2017)
Background: Picky eater is potentially at risk for nutritional deficits. In a long term, this habit could affect child’s growth and could lead to malnutritionObjective: This study was conducted to assess the association of maternal food variation, infant feeding practices, and pressure to eat with picky eating behaviors in 2-3 years old children.Method: In this cross-sectional study, mothers (n=141) of children aged 2-3 years old were recruited from 26 integrated health care centers in Gamping, Indonesia between Juni-September 2015 using a cluster random sampling method. Picky eater was calculated using Child Eating Behavior Questionnaire (CEBQ). Maternal food variation and early age feeding variability data were measured using food variation questionnaire. Data on the pressure to eat were obtained based on subscale pressure to eat in Child Feeding Questionnaire (CFQ). Mann-Whitney test was used to evaluate the association between maternal food variation, infant feeding practices, and pressure to eat with picky eating behavior.Results: Picky eater was significantly associated with mother pressure to eat (p<0,05). There were tendencies of shorter exclusive breastfeeding practice, later in the introduction of solid food, and fewer variability of food at an early age on picky eater, however, there was no significant association (p>0,05).Conclusion: Mother has a major role in forming children eating behavior. Not pressing children to eat, will protect children from picky eating.